Video-assisted liver ultrasound training for non-radiologists: protocol and preliminary results. Issue 6 (June 2021) - Jangsirikul, Sureeporn; Siripongsakun, Surachate; Chaiteerakij, Roongruedee
Abstract: Background: Ultrasound (US) is increasingly used as a bedside diagnostic tool, with training courses for non-radiologists being developed. However, the training time constraint is an important barrier for non-radiologists. We therefore created a short self-learning course for liver-US for non-radiologists. Aim: Assess the participants' ability in identifying the organ structures during a liver-US. Method: A short video-lecture on liver-US training and a portable guidebook for image acquisition were developed. Eighteen non-radiologist physicians studied the course and attended hands-on liver-US examinations to capture the assigned images and label the acquired organ/structures, which were evaluated by an expert radiologist. Result: 130 liver-US examinations were performed, 44 (33.8%) was cirrhosis. The overall of mean image acquisition score was 84.5 ± 9.7%. The mean score of the 1st examination was 75.2 ± 16.4. The mean score was >80% since the 2nd examination. The score was significant lower in cirrhotic cases as compared to non-cirrhotic cases (78.8 ± 17.3 vs. 88.3 ± 14.4, p  = 0.001). The participants' year of study and experience in previous US training did not affect the image acquisition score. Conclusion: The liver-US training course in a short video format with a portable guidebook is effective and relatively low time-consuming for teaching non-radiologists to perform bedside liver-US.